Evolution in Visual Communication of the Javanese Printed Wedding Invitations - Diah Kristina; Nur Saptaningsih (Humaniora, 2019)
Printed wedding invitations have been one of the most crucial aspects in the social organization among many countries like Brunei Darussalam, Iran, Egypt, and Persia. Javanese people also pay special attention to this social document as it represents social class, social status, prestige, and fnancial support allocated by the host. Evolution of printed Javanese wedding invitations represent social and economic pressures. The diasporic communities who were absent to earn a living brought a noticeable change by setting up the bride’s parents’ photographs in the invitations. 15 invitation texts were selected ranging from 1980 – 2017 used in Tawangmangu, Wonogiri and Sukoharjo, the eastern part of Central Java, Indonesia. There was a consistent regularity in terms of rhetorical structure. Functionally, the invitations have the same role of inviting prospective guests to share happiness in a more family-bound relationship. Inclusion of parents’ photographs, map of the location, pre-wedding photos, wise words, calendar, the profle of the couple were indicators of transformation taking place. Later, the printing decision of the invitations is pretty much customer-driven informed by the customers’ needs, values, and beliefs. Rhetorically the materialistically-driven social phenomenon was shown by an explicit gifts desired.